The “Instinct” of Imagination. A Neuro-Ethological Approach to the Evolution of the Reflective Mind and Its Application to Psychotherapy - Alcaro, Antonio; Carta, Stefano (Frontiers in Human Neuroscience, 2019)
Recent neuro-psychoanalytic literature has emphasized the view that our subjective identity rests on ancient subcortical neuro-psychic processes expressing unthinking forms of experience, which are “affectively intense without being known” (Solms and Panksepp, 2012). Devoid of internal representations, the emotional states of our “core-Self” (Panksepp, 1998b) are entirely “projected” towards the external world and tend to be discharged through instinctual action-patterns. However, due to the close connections between the subcortical and the cortical midline brain, the emotional drives may also find a way to be reflected within an intrinsic self-referential processing, evident when the organism is not actively engaged with the external world. Thanks to such endogenous functioning, the core-Self emotional dispositions are not overtly executed, but they are organized within coherent dynamic mental structures, called “feeling-toned complexes” by C. G. Jung and “unconscious phantasies” by Melanie Klein. The intrinsic self-referential dynamism of the “brainmind” originated from REM sleep arousal and then evolved in the resting-state activity of a complex of cortico-limbic midline brain structures (CMS), also called Default Mode Network (DMN). From our neuro-ethological perspective, it is sustained by an “introverted” SEEKING activity leading to the subjective exploration of internally constructed virtual scenarios. This “mind wandering” function, implicated in dreaming, fantasy processing, remembering and thinking, is the essence of the imaginative function and constitutes the first form of reflection, where intentions and drives gain a primordial form of conscious (but not self-conscious) representation. During postnatal development, this original (“archetypal”) imaginative function is slowly attuned in a relational “transitional” space and may be expressed first in non-verbal and eventually in abstract-verbal social communicative patterns. Our view has noticeable implications for psychotherapy. Instead of trying to directly modify interpersonal, extrinsic relationships (a top-down approach), dysfunctional emotional-relational patterns may be modified by a process in which the patient is helped to let-go of the perceived feeling-objects in favor of an immersion, via the actual feeling, from the superficial level of perception towards a void feeling-state, empty of images. Only starting from this “anoetic” feeling-state, the deep imaginal creative and re-structuring self-referential activity may be reactivated by a process of spontaneous imagination.